The ombudsman handbook designing and managing an effective problem-solving program - Ziegenfuss, James T. (McFarland & Co., Inc., 2011)
"This book presents the ombudsman in concept and practice, offering design and details from start-up to key activities and roles, as well as the benefits for the top executives, employees and customers. Case studies from numerous fields are examined to illustrate how a strong ombudsman program is vital to avoiding litigation, resolving conflicts and assisting management."--Provided by publisher.